Effect of Aging on Corrosion Behavior of Martensite Phase in Cu-Al-Be Shape Memory Alloy - Al-Haidary, Jafer T.; Aldulaimi, Ali M.; Hamza, Ahmed A. (Al-Nahrain Journal for Engineering Sciences, 2018)
The corrosion behavior of martensite phase in Cu-Al-Be shape memory alloy with aging at 150  at time 2,4and 6 hour and quenching ice water with salt, water at room temperature and oil media study by open circuit potential, tafal polarization and cyclic polarization. The microstructure of martensite study by optical microscope and x-ray diffraction(XRD) and transformation temperature was determined by Di?erential Scanning Calorimeter (DSC).the result show aging martensite at 150   at 2 and 4 hour have high open circuit potential, low corrosion current density , high corrosion potential and pitting potential than  martensite without aging.